2018
DOI: 10.1002/nau.23518
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tramadol on sneeze‐induced urethral continence reflex through μ‐opioid receptors in the spinal cord in rats

Abstract: These findings suggest that tramadol effectively enhances the AUR at the spinal level and BP peripherally. Therefore, stimulation of the spinal µ-opioid receptors may be useful for the treatment of SUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…These results suggest that glutamate stimulates both bladder and urethral functions. In our previous study, we reported that duloxetine, an inhibitor of norepinephrine‐ and serotonin‐reuptake, 22 and tramadol enhanced the sneeze‐induced urethral continence reflex in normal rats 13 . In the present study, residual urine was increased after tramadol administration in normal rats.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…These results suggest that glutamate stimulates both bladder and urethral functions. In our previous study, we reported that duloxetine, an inhibitor of norepinephrine‐ and serotonin‐reuptake, 22 and tramadol enhanced the sneeze‐induced urethral continence reflex in normal rats 13 . In the present study, residual urine was increased after tramadol administration in normal rats.…”
Section: Discussionsupporting
confidence: 63%
“…In our previous study, we reported that duloxetine, an inhibitor of norepinephrine-and serotoninreuptake, 22 and tramadol enhanced the sneeze-induced urethral continence reflex in normal rats. 13 In the present study, residual urine was increased after tramadol administration in normal rats. Thus, the activation of norepinephrine, serotonin, and µ-opioid receptor stimulation in the spinal cord can work as storage (i.e., inhibition of the bladder and stimulation of the urethra).…”
Section: Experiments 4: Evaluation Of the Ischemic Damagesupporting
confidence: 53%
See 1 more Smart Citation